Descolonizando o discurso da corrupção: uma análise do envolvimento do HSBC em corrupção transnacional - Nascimento, Isabella Chaves (2018)
Corruption is a problem with devastating human costs, it leads millions of people to poverty and death, and it can be a threat to national security by social discontent it has generated in many countries. It is not a phenomenon that can be attributed to nowadays, or any specific historical time to a neither political nor economic system being full of examples in all scenarios. Yet there are countries where corruption reaches other dimensions then researchers and authorities has striven to understand and somehow curb the phenomenon they claim to harm national growth and development. Organizations, laws and multilateral conventions with anti-corruption flag have arisen in this period besides criticism about the effectiveness of these mechanisms, due to the fact it attacked, primarily, demands side, not the offers side in global corruption equation. Demands side is known by NGO Transparency International definition as abuse of power granted for personal gains, reflecting political class interests but also the risks and the opacity of regulatory environment for business. In turn, the offers side is less questioned because bribe payments and money laundering rarely are criminalized, tax heavens continue protecting baking secrecy and a network of international players, with agents of the national financial system, allows dealers and corrupts keeping negotiating. This study is guided by post-colonial perspective, that see corruption construction in non-western countries as result of a complex set of practices and believes that had allowed singular ascendance in some nations regarding to the rest of the world, getting along to capitalists practices that leadsto dispossession and the subjugation of life and human dignity. From this perspective, recognizing informal transnational networks importance in perpetuation of corruption, is established this thesis general objective as comprehend beneath on the post-colonial lens, how corruption incorporate as a transnational phenomenon. We conducted a qualitative research, and we analyzed reports from the last ten years about corruption cases involving one of the world’s biggest bank: HSBC Holdings plc. In order to operate the research, we had been guided by two questions: (1) which are the standards and actors presents in transnational corruption dynamics? (2) which are the colonial relations that comes from these arrangements? The thematic analysis has resulted in forty-two categories and six groups of main actors that where associated in nine intermediate themes, indicating recurrent observed standards named as: operational manual, (un)wanted clients, disinformation, authorized justice, negligence, malpractice, dangerous liaisons, indifference and disruption. The research results shows a thematic final map and two final themes, which disclose colonial relationships presents on the arrangements: the complicit between financial system agents and offenders, and the colonizer impunity with these same agents.